The effects of scrap addition on the structure and precipitation hardening of hypereutectic Al-Fe alloys - Suwaree Chankitmunkong; Tawatchai Tangsuksan; Anastasia V. Tyurnina; Dmitry Eskin (IOP Conference Series Materials Science and Engineering, 2025)
Abstract Hypereutectic Al-Fe alloys represent a new group of alloys with promising properties, offering moderate strength, thermal stability, precipitation hardening capability and recyclability. In this study we used recycled beverage can scrap to produce Al-Fe alloys in order to demonstrate the suitability of these alloys for circular economy. Ultrasonic melt processing was applied to refine the structure. The scrap introduced impurities in the otherwise binary alloys, which modified the structure, improved strength and enabled precipitation hardening due to AlMnFeSi dispersoids and Mg-Si precipitates. The effects of scrap fraction in the alloy properties were quantified. This study highlights the potential of using recycled materials and advanced processing techniques to develop sustainable, high-performance aluminum alloys for a range of industrial applications.
Keywords: Aluminum Alloy Microstructure Properties; Aluminum Alloys Composites Properties; Advanced Welding Techniques Analysis